Adaptation, validation and reliability of the Massachusetts General Hospital-Sexual Functioning Questionnaire in a Colombian sample and factorial equivalence with the Spanish version (2016)
Sexual dysfunctions are a highly prevalent problem. It is necessary to have instruments adapted to the Colombian population in order to evaluate their sexual functioning because to date none of them have been validated. The aim of this study was to adapt and validate the Massachusetts General Hospital-Sexual Functioning Questionnaire in Colombian population, and compare it with a similar sample from Spain. Two different samples were used in this study. On one hand, a sample of expert judges who performed the cultural adaptation and the evaluation of the scale, and on the other hand, a second end sample of 1117 participants -men and women of both nationalities- who answered the questionnaire -together with others- through a virtual platform. Some of the items were adjusted based on the initial results of the evaluation by the expert judges. Cronbach's alpha between.81 and.92 were obtained after the application of the test. The psychometric properties of the scale are adequate and this instrument properly correlates with other criterion variables. Construct validity was evaluated using factorial invariance. The unidimensional configural model for men (RMSEA =.000; CFI = 1) and for women (RMSEA =.048, CFI =.997) had an adequate fit, and a level of strict invariance was also reached. Screening can be performed with this first validated scale in order to evaluate the sexual difficulties of the Colombian population and compare them with the Spanish population. © 2016 Fundación Universitaria Konrad Lorenz.